Centrifugal Pump Shaft Coupling Durability Material S45C in the Water Treatment Plant Unit with the Destructive Test Method (impact) - Muhammad Fajar Lubis; Nuzuli Fitriadi; Fransnazoan Sitorus (Jurnal Inotera, 2023)
The peg is a component that functions as a binder between the shaft and the hub in transmitting power and rotation. In general, the pegs are designed and made using metal materials such as mild carbon steel. In this research, the material of the coupling pin design on the centrifugal pump shaft is S45C. Where on the sample of the designed post, an impact test or the Charpy method of hitting the notch is carried out which aims to determine the amount of resistance to sudden loading and to determine the physical changes (failure modes) experienced by the post material. In this study, the sample of the post with dimensions of 6.10 mm x 6.10 mm x 55 mm obtained a large impact strength (impact strength) in the Charpy method impact test of 0.8445 Joule/mm2. And for the physical change (failure mode) experienced by the post material against the sudden loading, it is a brittle fracture that is characterized by physical characteristics in the form of granular (like sand) on the fracture surface, and the absence of plastic deformation that occurred first.